Drop In - Lemke, Donald B.; Majado, Caio (Mankato, Minn. : Stone Arch Books, 2012)
Omar Grebes and his friend Tommy Goff are both reckless skateboarders, but when they become involved with a mysterious organization called The Revolution, things get confusing and dangerous.
Accelerated Reader AR
Keywords: Skateboarding -- Fiction; Secret societies -- Fiction; Best friends -- Fiction; Imperial Beach (Calif.) -- Fiction; Fiction